Preparation, properties and grouting process simulation of cement-based grout for loose deposits - Jian, Li-Ming; Zhao, Xiao-Yan; Wu, Jiang; Yan, Hong-Yi; Wan, Yu-Hao; Wang, Sheng; Zhang, Chun; Long, Rui-Xin (Construction & building materials, 2022)
•A new solution for leakage plugging in loose strata was brought out.•A newly designed simulation device for evaluating the grouting effect was introduced.•The prepared formula LCP was successfully applied to the lab simulation test.•The pugging process of LCP in leakage channels was revealed. In the case where grout is used in loose strata, the leakage is crucial to the control of plugging efficiency in the seepage channel. However, the existing grouting materials generally have insufficient properties to meet the engineering requirements in such conditions. Therefore, the present study developed a new cement-based grouting material on the basis of theoretical analysis and experimental investigation. With high adhesion ratio and rapid setting characteristics, the proposed grouting material can stick to the seepage channel with high proportion, thus plugging these channels rapidly. To this aim, based on the compounding of Portland cement with sulphoaluminate cement and the introduction of cement-modified admixtures, such as hydroxyethyl cellulose and sodium polyacrylate, the preparation of grouting formula by the factorial experiment design was comprehensively investigated. This method, the harmonized relationship among adhesion ratio, workability time and mechanical characteristics of the proposed formula was established. Simultaneously, the engineering application feasibility of the proposed grout mixture was verified from both qualitative and quantitative aspects by a newly designed grouting simulation set-up. Finally, the plugging mechanism of this grouting formula in seepage channels was further concluded by monitoring the change of grouting parameters and calculating the plugging efficiency of the injected medium. This study provides a new method to enhance the plugging efficiency of seepage channels in loose deposits by improving the properties of potential cement-based grouting materials.